A reciprocal music pedagogy of rhythmic care: The decolonial voices of Paulo Freire and Yusef Waghid - Sergio Garcia Cuesta (Nordic Research in Music Education)
This article explores the link between the voices of Paulo Freire and Yusef Waghid and their potentialities for music education, focusing on the overarching themes of (a) criticality and scepticism in collaboratively reviewing learned oppressions, (b) the teacher-student/student-teacher as a hybrid category, (c) the importance of dissonance and presence in a caring dialogical education, (d) the potentials of rhythmic care in music education, and (e) ubuntu care: the self and the other. This text concludes by briefly proposing the concept of ‘a reciprocal music pedagogy of rhythmic care’, and its possible application to Nordic music education contexts, as a way to incorporate the inspiration drawn by the philosophies of these two scholars on a practical level.